2017
DOI: 10.1111/jnu.12292
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Nurse Staffing and Patients’ Experiences, and the Mediating Effects of Missed Nursing Care

Abstract: Appropriate nurse staffing is required to reduce missed care and to improve patients' experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 13 publications
(17 reference statements)
1
68
3
1
Order By: Relevance
“…In addition, a small number of cross-sectional studies published during the current project have demonstrated that associations between low nurse staffing and adverse patient outcomes, including falls, patient experience and mortality, are mediated by nurses' reports of missed care. [23][24][25][26] Although they provide more direct evidence of a causal pathway, these studies have, thus far, relied on intermittent, retrospective nurse reports of missed care, which must be regarded as subjective measures. Taken as a whole, these studies do suggest that care omissions may provide more direct indicators of nurse staffing adequacy, which are, in turn, related to important outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small number of cross-sectional studies published during the current project have demonstrated that associations between low nurse staffing and adverse patient outcomes, including falls, patient experience and mortality, are mediated by nurses' reports of missed care. [23][24][25][26] Although they provide more direct evidence of a causal pathway, these studies have, thus far, relied on intermittent, retrospective nurse reports of missed care, which must be regarded as subjective measures. Taken as a whole, these studies do suggest that care omissions may provide more direct indicators of nurse staffing adequacy, which are, in turn, related to important outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous analysis focused on patients (ie, patientreported missed care and patient experiences) was published elsewhere (Cho et al, 2017) The study examined the relationships among nurse staffing, missed care reported by nurses and patients, patient experiences, and nurse outcomes.…”
Section: Design and Samplementioning
confidence: 99%
“…The study examined the relationships among nurse staffing, missed care reported by nurses and patients, patient experiences, and nurse outcomes. A previous analysis focused on patients (ie, patientreported missed care and patient experiences) was published elsewhere (Cho et al, 2017), whereas the current study focused on nurses. A notice of request for participation in the study was mailed to 183 hospitals by the Korean Hospital Nurses Association, and 52 hospitals agreed to participate in the study.…”
Section: Design and Samplementioning
confidence: 99%
See 2 more Smart Citations